Prenatal Diagnosis and Perinatal Management Considerations in Congenital Abdominal Wall Defects: A Case Series and Narrative Review - Nikola Popovski; Nikoleta Stoyanova; Rebecca Caiulo (Journal of Personalized Medicine, 2026)
Background: Congenital abdominal wall defects (CAWDs), primarily gastroschisis and omphalocele, result from disturbances in early embryonic folding and midgut development and are routinely detected during prenatal ultrasound screening. Despite advances in prenatal imaging, considerable heterogeneity in clinical presentation, severity, and outcomes necessitates structured risk stratification to optimize prenatal and perinatal management. Objectives: We aimed to present a series of prenatally diagnosed congenital abdominal wall defects and integrate current evidence into a clinically applicable, risk-adapted framework for prenatal assessment and perinatal management. Materials and Methods: Three pathological cases of CAWDs diagnosed between 2025 and 2026 were retrospectively analyzed. Two additional first-trimester ultrasound examinations demonstrating physiological midgut herniation were included as illustrative examples of an important differential diagnosis during early pregnancy. Prenatal assessment included systematic evaluation of bowel dilatation, bowel wall thickness, liver herniation, and associated structural anomalies. Established risk stratification systems—including the distinction between simple and complex gastroschisis and the classification of omphalocele according to defect size and associated anomalies—were applied. A narrative review of the literature was performed to contextualize the clinical findings and support the development of a practical ultrasound-based diagnostic and management algorithm. Results: The pathological cases illustrated the broad clinical spectrum of CAWDs, ranging from isolated omphalocele to lethal body stalk anomaly, while the illustrative examples emphasized the importance of distinguishing physiological midgut herniation from pathological abdominal wall defects during the first trimester. Prenatal risk stratification based on ultrasound findings may inform surveillance strategies, delivery planning, and parental counseling. In particular, associated anomalies and liver herniation in omphalocele, as well as progressive bowel abnormalities in gastroschisis, were identified as key determinants of prognosis and clinical management. Based on the literature review and the illustrative institutional cases, an educational ultrasound-based diagnostic and management framework was proposed to summarize the current evidence and support a structured diagnostic approach. Conclusions: Congenital abdominal wall defects should be considered a spectrum of disorders with varying embryological origins, clinical manifestations, and prognostic implications. A standardized prenatal assessment combined with risk-adapted management can improve prognostic accuracy, optimize perinatal planning, and support informed parental counseling. Implementation of structured diagnostic frameworks may enhance clinical decision making and improve outcomes in affected pregnancies.